Examining the factors leading to rising unemployment rate during the COVID-19 pandemic - Choo, Zhan Jing; Chua, Xiao Woon; Ooi, Yee Chern; Wong, Suet Yee (2021)
A study on factors leading to rising unemployment rate during the COVID-19 pandemic. To examine the overall effect of the COVID-19 outbreak on the unemployment rate, policymakers’ decision in suppressing the rising unemployment rate and effects of economic activity to the unemployment rate. We used Pooled ordinary least square model (POLS), fixed effect model (FEM) and random effect model (REM) to examine our empirical models. There are 14 countries which are Australia, Brazil, Canada, Denmark, Finland, Germany, Ireland, Italy, Japan, Malaysia, Russia, Switzerland, the United Kingdom and the United States, have been adopted as our sample size with the time period of 10 months, from 1st February 2020 until 31st November 2020. In the study, we analyse how the impacts of independent variables which are economic activity, fiscal policy, COVID-19, internet accessibility and stock market return to the unemployment rate in 14 countries. Our major findings showed workplace mobility and government spending bring negative impacts to unemployment rate, while number of COVID-19 cases, stock market return, internet accessibility and residential mobility reflect positive impacts to unemployment rate. This study serves as a lesson for the future on what is the right thing to be done in order to soften the impact of the pandemic towards the unemployment rate.